Drivers of Long-Term Insecurity and Instability in Pakistan Urbanization - Blank, Jonah (RAND Corporation, 2014)
Pakistan is already one of the most urbanized nations in South Asia, and a majority of its population is projected to be living in cities within three decades. This demographic shift is likely to have a significant impact on Pakistan's politics and stability. This report briefly examines urbanization as a potential driver of long-term insecurity and instability, with particular attention to the cities of Karachi, Lahore, and Quetta.